Dialectics of Classicism: The birth of Nazism from the spirit of Classicism. (June 2019) - Redner, Harry
This article is an attempt to revise and extend two prior conceptions: Adorno and Horkheimer's dialectic of Enlightenment and Murphy and Robert's dialectic of Romanticism. It traces a developmental trajectory within German Kultur, starting around the mid-18th century, that goes through three moments or phases: the Grecophilia of Goethe and Schiller, the Grecomania of Hölderlin, Schelling and early Hegel, and the Grecogermania of Wagner, Nietzsche and Heidegger. The latter provided the ideological underpinning of Hitler's Nazism. Thus the paper aims to show that Nazism had deep roots within the soil of German Kultur, for almost from the very start Classicism and anti-Semitism were integral aspects of the one cultural movement. Furthermore, this movement was the one surrogate form of a Neo-Pagan and anti-Christian trend in German modernity.